A discursive exploration of public perspectives on placebos and their effects. Issue 1 (February 2019) - Hardman, Doug I; Geraghty, Adam WA; Howick, Jeremy; Roberts, Nia; Bishop, Felicity L
There is increasing evidence that placebos could be effective in clinical practice. However, knowledge of public perspectives on placebos is underdeveloped. We conducted a discourse analysis of internet comments on news articles related to placebos, aiming to improve this knowledge for clinicians and researchers. We developed two discursive constructs of the placebo. The dominant construct of the 'placebo pill' informs a paradoxical understanding of placebos that closes down treatment. The less-prevalent counter-discursive construct of the 'treatment process' frames placebos as potentially viable within modern evidence-based medicine. We discuss the opportunities and challenges of this alternative understanding of placebos.